2011
DOI: 10.3109/10408363.2011.580567
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and behavioral aspects of the actions of alcohol on the adult and developing brain

Abstract: The brain is one of the major target organs of alcohol actions. Alcohol abuse can lead to alterations in brain structure and functions and, in some cases, to neurodegeneration. Cognitive deficits and alcohol dependence are highly damaging consequences of alcohol abuse. Clinical and experimental studies have demonstrated that the developing brain is particularly vulnerable to alcohol, and that drinking during gestation can lead to a range of physical, learning and behavioral defects (fetal alcohol spectrum diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
142
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 394 publications
6
142
0
3
Order By: Relevance
“…En cambio el consumo excesivo podría asociarse con alteraciones del desarrollo neurológico 171 y de la función motora 172 . Por su parte los estudios experimentales sugieren que el alcohol causa alteraciones estructurales irreversibles sobre el cerebro en formación, afectando a mecanismos genéticos, moleculares y celulares [173][174][175] .…”
Section: Problemas Perinatalesunclassified
“…En cambio el consumo excesivo podría asociarse con alteraciones del desarrollo neurológico 171 y de la función motora 172 . Por su parte los estudios experimentales sugieren que el alcohol causa alteraciones estructurales irreversibles sobre el cerebro en formación, afectando a mecanismos genéticos, moleculares y celulares [173][174][175] .…”
Section: Problemas Perinatalesunclassified
“…However, studies have confirmed that alcohol may damage specific regions both in the adult and the adolescent brain (Alfonso-Loeches and Guerri, 2011). The mechanisms behind this damage is suggested to involve excitotoxicity, free radical formation and neuroinflammatory destructions caused by activation of the immune system and mediated through Toll-like receptor 4 (TLR4 receptor).…”
Section: Alcohol-induced Effects On Memory and Cognitionmentioning
confidence: 99%
“…The effects of alcohol in the brain are not uniform, affecting mainly the pre-frontal cortex, the hippocampus, the cerebellum, the substantia nigra and the glia 27 . Dopaminergic neurons in the substantia nigra are believed to be damaged by alcohol during intrauterine development 27,28 . The effect of alcohol in this region is still unclear concerning brains are already developed 28 .…”
mentioning
confidence: 99%
“…Likewise, association between I/I genotype and alcoholism was found in familial PD patients. Admittedly, alcohol abuse damages brain structures and their functions, which leads to neurodegeneration 27 . The effects of alcohol in the brain are not uniform, affecting mainly the pre-frontal cortex, the hippocampus, the cerebellum, the substantia nigra and the glia 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation